Capital regulation and bank capital ratio – introduction of a new measurement. Issue 6 (2nd November 2021) - Nguyen, Quang Thi Thieu; Gan, Christopher; Li, Zhaohua
ABSTRACT: This study examines how capital regulation affects bank capital ratio in Asia during the period 2001–2015. Employing a new capital regulation measurement and System Generalized Method of Moments estimation, our study shows that: (i) Capital regulation has been effective in inducing banks to raise capital ratios; (ii) Bank capital ratios are affected by bank characteristics and macro-economic factors, similar to non-financial firms; (iii) The effects of bank characteristics and macro-economic factors vary across banks in developed, emerging and frontier countries, as well as countries with and without Basel Committee membership.